HUBUNGAN PERILAKU PERSONAL HYGIENE DENGAN KEJADIAN KEPUTIHAN PADA WANITA PENYANDANG DISABILITAS DI HWDI SLEMAN - jumarnis, monika (Jurnal Ilmiah Bidan (JIB), 2025)
Abstrack Basic health needs for women with disabilities are being able to carry out self-care activities including genitalia known as personal hygiene. Personal hygiene is personal hygiene care to prevent infections caused by bacteria, especially genitalia which are susceptible to infection. This study aims to determine the relationship between personal hygiene behavior and the incidence of vaginal discharge in women with disabilities at HWDI Sleman. The method in this study is correlational with a cross-sectional approach. The respondents of the study consisted of 40 members of HWDI Sleman and were taken using a purposive sampling technique with the inclusion criteria of experiencing vaginal discharge in the last 6 months. Data collection used a questionnaire and a chi-square test was carried out. The results of this study showed that most respondents had good personal hygiene behavior of 50% and the incidence of vaginal discharge was mostly physiological vaginal discharge of 50%. The chi-square test analysis obtained p = 0.003 which means p <0.05 meaning that there is a significant relationship between personal hygiene behavior and the incidence of vaginal discharge in women with disabilities. Keywords: Personal hygiene, vaginal discharge, women with disabilities